Improvement of medical-pedagogical observation as a method for preventing the development of prepathological condition in young athletes - Usmankhodjaeva, Adiba A. (International Journal of Research in Medical Sciences, 2017)
Background: In the practice of training young athletes in recent years, there has been a tendency to one-sided development. Currently, existing protocols, medical-pedagogical surveillance (MPS) is imperfect, do not enable to collect complete information about young athlete in the course of training which required for the correction of the training process and optimise post-physical stressing recovery. Aim of the study is to assess the effectiveness of the improved protocol implementation- medical-pedagogical observations of children engaged in sport schools in Uzbekistan. Methods: The study was performed over 120 sports school students. Medical-pedagogical supervision (MPS) was conducted in the morning and evening sessions in different periods of the annual cycle. Study participants were divided into 2 groups and each includes 60 people, depending on the applied Protocol MPS. During the training, led timing classes, noted what the athlete using a symbol. At the end of training calculated duration of physical stress and motor density lesson finding the percent of the time the physical stress to the total training duration. Special attention was paid to the nature of the training process: the number of lessons per week correct their location, the duration and structure of activities, their common and motor density. During exercise, every 10-15 minutes counting the pulse. Results: Density of the training depended on the degree of preparedness of young athletes and in the elementary group it was 58%, middle- 63%, high- 70%. According to the current Protocol MPS failed to identify the presence of fatigue of young athletes and to assess its degree. In middle physical stress distributed such a way that the ratio of general physical training and special physical stress was equal parts, warm-up was 18-20%, the majority- 60%, final was 15-18%. In older group warm-up 10-15% of the entire training duration, the major part- 80% and the final 5-10%. The density classes are 65-80%. Reorganization showed that the number of basic groups of chronic diseases was decreased 1.2-2.5 times in most classes of diseases, whereas in control group these indicators in 2015, by contrast, has grown in 1.5-2.2 times in comparison with 2014. Conclusions: Conduct medical-pedagogical supervision on advanced protocols and corresponding reorganization of the training process and rationalization of physical stress allowed to improve the dynamics of their physical development without deviations from age-related standards of physical fitness and reducing rates of infection.